5α‐Dihydrotestosterone negatively regulates cell proliferation of the periurethral ventral mesenchyme during urethral tube formation in the murine male genital tubercle. (1st October 2016) - Suzuki, H.; Matsushita, S.; Suzuki, K.; Yamada, G.
Summary: Androgen is an essential factor involved in masculinization of external genitalia. Failure of the exposure to 5α‐dihydrotestosterone (DHT) causes a hypoplastic penile size and urethral abnormality. The main pathology of hypospadias is defective urethral closure on the ventral side of the penis. Hormone‐dependent genes are suggested as the causative factors. However, the detailed mechanisms of DHT functions on urethral tube formation remain unknown. Androgen is both a positive and negative regulator of cell proliferation. The roles of locally converted DHT in cell proliferation at the periurethral mesenchyme have not been elucidated. We revealed the expression pattern of 5α‐reductase type 2 mRNA ( Srd5a2 ) and local DHT distribution by direct measurement in this study. We also analyzed periurethral mesenchymal cell proliferation status using systematic three‐dimensional (3D) reconstruction analyses. A prominent Srd5a2 expression and localized DHT distribution on the ventral side of the genital tubercle were detected. Cell proliferation was reduced in this mesenchymal region during urethral formation. The current results suggest the presence of the possible negative regulation of cell proliferation by DHT. Moreover, cell proliferation related to urethral tube formation was revealed to be DHT dose dependent. These data are expected to contribute to the understanding of the mode of regulation of cell proliferation related to urethral tube formation by DHT. These findings may also offer insight into the understanding of human hypospadias and related hormone‐dependent factors.